Management of Energy Enterprises: Energy-efficiency Approach in Solar Collectors Industry: The Case of Russia - Ratner, Svetlana; Chepurko, Yuri; Drobyshecskaya, Larisa; Petrovskaya, Anna (International Journal of Energy Economics and Policy, 2018)
In the last few years, the development and management of some types of renewable energy industries in Russia is proceeding at a rapid pace, mainly due to government support programs. At the same time, many renewable energy technologies designed for use at the enterprises, primarily in the residential and commercial sectors, have not yet been widely disseminated. In particular, this applies to solar collectors. In this article, we study the factors, preventing the wider distribution of solar collectors in the residential sector from the viewpoint of the theory of energy-efficiency. The focus of research is the informational barriers. The obtained results allow us to draw several practical conclusions about the directions for improving regional energy-efficiency programs currently being implemented in most of Russian regions. Keywords: solar thermal energy, solar collectors, barriers of energy efficiency, survey JEL Classifications: O33, Q42, Q47, Q48